An Interview with the Founder/CEO of Psaltry International ltd - International Institute of Tropical Agriculture (IITA, 2023)
Mrs. Iranloye, Founder and CEO of Psaltry International takes the IITA Communication team through her agribusiness journey and how IITA has been part of her success story in over two decades.